Państewko Gabriele d’Annunzio — ustrój Włoskiej Regencji Carnaro - Rakowski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The subject of the study is the constitutional regime of the independent city of Fiume during the authoritarian rule of Gabriele D’Annunzio (September 1919 — December 1920). His power was based not on legal norms, but on the will of the commander known as the prophet (vate) or the leader (duce), supported by the strength of his army. Nevertheless, in September 1920, D’Annunzio proclaimed the Charter of Kvarner — the constitution of the small state, which never came into force. The author analyzes its provisions using the formal-dogmatic approach, pointing to the modernity and originality of its regulations: gender equality, guarantees of social rights, protection of work, secularity of education, society divided into corporations, elements of direct democracy, division of powers between legislative chambers, and a lack of the head of state. Constitutional institutions are presented with consideration of the history of Fiume, studied by the historical approach. The author concludes that D’Annunzio did not belong to the fascist movement, but was rather a rival of Mussolini, with a different vision of the state and methods of rule. His Charter of Kvarner can therefore be seen as a concept for the new Italy. At the same time, the commandant was a forerunner of the methods of communicating with society which were later used by the leaders of totalitarian states.
Keywords: Fiume; Rijeka (Fiume) (Chorwacja); Gabriele D’Annunzio; Regencja Carnaro; Cartadi Fiume